2015
DOI: 10.1515/jas-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Tyrosinase Inhibitory Properties of Aqueous Ethanol Extracts from Monofloral Bee Pollen

Abstract: A b s t r a c t Bee pollen has been used for many years in traditional medicine and supplementary nutrients. Bee pollen is mainly composed of nutrients and bioactive substances which might act as potential antioxidants and tyrosinase inhibitors. In this study, 14 species of monofl oral bee pollen from China were collected to analyse their antioxidant and tyrosinase inhibitory properties. Our results revealed that virtually all the bee pollen samples possessed powerful antioxidant or tyrosinase inhibitory activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…Schisandra chinensis bee pollen has been widely accepted as a functional food in China for several decades. Studies have confirmed its powerful antioxidant capacity among 14 species of monofloral bee pollen from China [22]. Besides this, S. chinensis bee pollen has also been reported to possess the strongest total antioxidant capacity among ten kinds of bee pollens based on Trolox equivalent antioxidant capacity, reducing power, and DPPH• radical scavenging activity [23].…”
Section: Introductionmentioning
confidence: 99%
“…Schisandra chinensis bee pollen has been widely accepted as a functional food in China for several decades. Studies have confirmed its powerful antioxidant capacity among 14 species of monofloral bee pollen from China [22]. Besides this, S. chinensis bee pollen has also been reported to possess the strongest total antioxidant capacity among ten kinds of bee pollens based on Trolox equivalent antioxidant capacity, reducing power, and DPPH• radical scavenging activity [23].…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro antityrosinase activity was determined as previously reported (Zhang et al, 2015) with minor modification. Five different concentrations of the respective test sample dissolved in dimethyl sulfoxide (DMSO) were prepared.…”
Section: In Vitro Antityrosinase Activitymentioning
confidence: 99%
“…The bee pollen of Schisandra chinensis (Turcz.) Baill, which is often used as a functional food in China, has been found to possess a strong antioxidant activity [ 15 – 17 ]. Our recent study revealed the antioxidative and cardioprotective effects of S. chinensis bee pollen extract (SCBPE) on isoprenaline-induced myocardial infarction in rats [ 18 ].…”
Section: Introductionmentioning
confidence: 99%